Règle de conduite de politique monétaire applicable a la BEAC - Ngakosso, Antoine (DEMO, 2018)
The object of this paper is to put forward a reaction function concerning the behavior of the Bank of the Central African States (BEAC). The empirical results show that, with the exception of output gap, all other variables have a significant influence on the interest rate. In addition to this, there is an error-correction mechanism indicating convergence towards equilibrium level of interest rate.(original abstract)
Keywords: State banks; Monetary policy; Chartered Financial Analyst (CFA); Exchange rates; Dollar; United States dollar (USD)